1995
DOI: 10.1093/ajcp/103.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Ploidy Analysis of Products of Conception by Image and Flow Cytometry With Cytogenetic Correlation

Abstract: Ploidy analysis of hydropic placentas is used in conjunction with morphology and clinical data to classify hydatidiform moles and hydropic abortuses. In most studies, ploidy has been assessed by flow cytometry (FCM). To validate image cytometry (ICM) as a method to determine ploidy in this setting, the authors used both FCM and ICM to study 19 hydropic placentas in which cytogenetic analysis was available. Nuclear suspensions from paraffin-embedded tissue were used for both ICM and FCM. Image cytometry of tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…On occasion, it can be difficult to distinguish a true triploid cell population from an actively dividing diploid cell population by FC, and this can lead to a false-negative diploid result in a patient with a PM. 12 In our study, there were 3 PM specimens that were interpreted as triploid by DIA and FISH and diploid by FC. These false-negative results could be due to extensive The combined findings of our study strongly suggest that the combination of FISH and p57 immunostaining results provide the most accurate identification of CM, PM, and HA specimens.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…On occasion, it can be difficult to distinguish a true triploid cell population from an actively dividing diploid cell population by FC, and this can lead to a false-negative diploid result in a patient with a PM. 12 In our study, there were 3 PM specimens that were interpreted as triploid by DIA and FISH and diploid by FC. These false-negative results could be due to extensive The combined findings of our study strongly suggest that the combination of FISH and p57 immunostaining results provide the most accurate identification of CM, PM, and HA specimens.…”
Section: Discussionmentioning
confidence: 62%
“…[12][13][14][15][16]21,27 Because HA and CM specimens characteristically consist of diploid or near-diploid chromosomal complements, FC and DIA cannot reliably distinguish HAs from CMs. However, a triploid interpretation by FC or DIA is considered diagnostic of a PM because most PMs consist of an androgenic triploid chromosomal complement.…”
Section: Discussionmentioning
confidence: 99%
“…This is advantageous for the evaluation of early small cancer from which a few tumor cells are available, or for specimens contaminated with normal host-derived cells. In image analysis, cytospin preparations allow better resolution than other preparations (8). In this study, however, we used touch preparations, since one of our aims is to apply this technology to archival smears as well as to fresh specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In samples heavily contaminated by maternal cells, small populations of triploid cells may be overlooked 18 . A number of studies have shown that image cytometry can be applied to the assessment of ploidy in hydatidiform moles, with high concordance with flow cytometry 14,19 , 20,30–32 . In a study of 53 molar pregnancies, Berezowsky et al 31 .…”
Section: Image Versus Flow Cytometrymentioning
confidence: 99%
“…This technique evaluates fewer cells (typically 200–300) and so has lower resolution but offers greater specificity. It is time‐consuming, however, especially when undertaken manually 14,19 , 20 …”
Section: Introductionmentioning
confidence: 99%